Positive Paradigm As The Barrier of Art Creativity Interpretation (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
In the modern era, during the end of 17 century, appears empiric paradigm in the philosophy field. This paradigm emerges due to the critic towards mythical social thought. The next step appears positivism thought by Auguste Comte in 1830, which stated that Sociology based on science analogy that can be learned in the form of empiric data with exact calculation; out of this is rated as not scientific. The education field also trails the modern thought tradition, along with Comte’s positivistic thought. This modern era eventually has been opposed by postmodern philosophers. The frailties in the modern era are criticized by the appearance of the postmodern paradigm. Positivistic thought, in reality, could not reveal study beyond human and society, because this study is strong, and can only reach the ontologic stage, in substance of the object. While this could not be revealed because its level involves human and society’s way of thinking, primordial, tradition, and historical aspects, this study focuses on the weaknesses of positivistic research. Then it will present post-positivistic-postmodern research through Hermeneutika and Foucauldian Genealogy research.